EFEKTIFITAS MACAM PUPUK KANDANG DAN KONSENTRASI AIR KELAPA TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) - Dian Eka Kusumawati; Arga Ardhiansya; Choirul Anam; Mutiara Kusumaningtyas Pitaloka (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
Shallots have a significant role in horticulture, being used both as a spice and in medicine. Demand continues to grow in Indonesia. This research focuses on the use of nutrient-rich manure and coconut water which is rich in vitamins and essential nutrients to support the growth of shallots. This research used a factorial Randomized Block Design (RAK) which was repeated three times. There are two main factors of concern in this research. The first factor is the type of fertilizer (K), which includes three different formulas, namely cow manure (K1), goat manure (K2), and chicken manure (K3). The second factor is the concentration of coconut water (A), which has three different levels, namely without treatment (A1), coconut water concentration of 250 ml plus 750 ml of pure water (A2), and a mixture of 500 ml of coconut water with 500 ml of water (A3). Research findings show that the combination of manure type and coconut water content affects the growth and yield of shallot plants. The use of chicken manure together with coconut water content of 50% produced the best results in this study.